A Fun Teacher for Students in Learning English - Andika Andika (English Education : English Journal for Teaching and Learning, 2026)
This study aims to describe the characteristics of a pleasant teacher based on students' perceptions and its impact on the English learning process. A descriptive qualitative method was employed involving 15 tenth-grade students at MA Ash-Shiddiqiah. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The findings reveal that a pleasant teacher is characterized by being friendly, patient, humorous, empathetic, fair, tolerant, calm, understanding of students' characteristics, and capable of delivering lessons in a creative, engaging, and understandable manner. Such teachers also provide motivation, support, and appreciation to students. These characteristics positively influence the learning process by increasing students' motivation, creating a comfortable and supportive classroom atmosphere, enhancing comprehension, building self-confidence, reducing learning boredom, and improving academic achievement. The findings suggest that pleasant teacher characteristics contribute not only to students' emotional and psychological well-being but also to their academic success. Therefore, teachers should continuously develop their personal and social competencies alongside professional competencies to create an effective and positive learning environment that supports the achievement of educational goals.